Indonesia’s Military Reserve: Legislative, Ethical, and Operational Challenges - Hastuti, Lina; Camelia, A. Indah (Faculty of Law, Universitas Brawijaya, 2025)
In light of the decreasing conventional military threats and the increasing non-military disputes, the need for a comprehensive defence that incorporates diverse national resources is underscored. However, the establishment and integration of a reserve component within the national military framework in Indonesia creates many challenges. The paper examines the context of reserve forces globally then compare with Indonesia’s under Law No. 3/2002 concerning National Defence and Law No. 23/2019 regarding the Management of National Resources for National Defence. It critically analyses the legal, ethical, and operational complexities surrounding the reserve component. highlighting the ambiguities in its role alongside conventional armed forces and the implications for accountability, human rights, and adherence to humanitarian law. It is normative legal research, utilising qualitative analysis to assess current policies, regulations, and the intersection of legal frameworks with ethical considerations. The findings reveal significant gaps in the legal framework governing Indonesia's reserve forces, particularly regarding mobilisation procedures, contract durations, and the dual status of reservists as both civilians and combatants.